Prenatal Diagnosis of a Persistent Fifth Aortic Arch, Pulmonary‐to‐Systemic type: An Unusual Association with Evolving Aortic Coarctation. Issue 5 (21st November 2014) - Bhatla, Puneet; Chakravarti, Sujata; Axel, Leon; Ludomirsky, Achi; Revah, Giselle
Abstract : Persistent fifth arch (PFA) is a rare anomaly that is often underdiagnosed and missed. Different PFA types that have been reported in the literature are systemic‐to‐systemic type (most common), systemic‐to‐pulmonary artery (PA), and PA‐to‐systemic types. The designations of systemic‐to‐PA or PA‐to‐systemic are based on if the PFA is a source of PA or systemic blood flow, respectively, in the setting of critical proximal obstruction (pulmonary atresia or aortic atresia). This case describes an unusual PFA, which connects the distal PA to distal ascending aorta; however, it is not associated with critical proximal obstruction, and while it appeared to be an incidental finding in early gestation, progressive serial distal obstruction of the left fourth arch was seen to develop. This case highlights that prenatal diagnosis of PFA is possible and that once a diagnosis is made, serial fetal echocardiograms should be performed to evaluate for evolving lesions. Mini‐Abstract: Persistent fifth aortic arch can be diagnosed antenatal by fetal echocardiography. Identification of this anomaly should prompt serial prenatal follow‐up to diagnose evolving lesions, which can aid in better delivery planning and anticipate emergent postnatal interventions.